Hand grip strength and quality of life among adults aged 50–90 years from South West Poland - Antonina Kaczorowska; Sławomir Kozieł; Zofia Ignasiak (Scientific Reports)
Abstract With advancing age, progressive loss of muscle strength, as assessed by hand grip strength, may result in a poorer health-related quality of life. The aim of this study is to determine the associations of hand grip strength with quality of life among people aged 50–90 years from South West Poland. The study group comprised 1 446 people, including 351 men and 1 095 women, aged between 50 and 90 years. The WHOQoL-BREF questionnaire was used to assess quality of life. Hand grip strength of the dominant hand was measured. The general assessment of quality of life shows a significant relationship with hand grip strength. Two domains of quality of life: social and environmental also significantly differentiate hand grip strength. As the number of points in given domains increases, the hand grip strength increases. Among men, the relationship between the environmental domain and hand grip strength is significantly stronger compared to women. Hand grip strength is related to the quality of life among older adults, especially in the social and environmental domains. The results of our study suggest that measures need to be taken to improve the strength of skeletal muscles in adults, which might improve their quality of life.